Polemics on Interfaith Marriage in Indonesia between Rules and Practices - Ermi Suhasti; Siti Djazimah; Hartini Hartini (Al-Jami'ah Research Centre, 2018)
The Indonesian rules on marriage manage that a marriage is required to be one faith marriage, i.e., a man and woman to embrace the same religion, and prohibits interfaith marriage. However, in practice interfaith marriage is concluded and the couple of such marriage struggled to conduct the marriage and to have the marriage legitimized. One of the ways is to propose a designation or decree from the civil court to officially allow them to marry and to mandate the Civil Marriage Registrar to register their marriages. This article discusses the practice of interfaith marriages based on the permission from the civil courts’ judges in Surakarta. Deploying the socio-legal approach and based on interviews with some relevant persons and on the observation on a number of civil courts’ decrees, this article finds that there are interfaith marriages in Indonesia and interfaith couple struggled to get their marriages officially admitted and legalized by taking the advantage of the legal gap on the issue. This article also argues that there has been divergent legal interpretation within Indonesians which led to legal uncertainty regarding the rules of interfaith marriage in Indonesia.[Peraturan tentang perkawinan di Indonesia mengatur pernikahan satu agama. Pernikahan harus antara wanita dan laki-laki Muslim dan larangan pernikahan beda agama. Banyak praktik pernikahan melakukan ikatan beda agama. Pernikahan ini diilakukan para pasangan dengan berupaya keras dengan cara apapun untuk dapat menikah secara formal. Salah satu cara dengan memohon ijin melalui putusan Pengadilan Negeri. Pengadilan memberikan ijin pernikahan beda agama dan mandat kepada pegawai Pencatat Sipil untuk dicatatankan sebagai pernikahan. Artikel ini mengkaji praktik pernikahan beda agama melalui penetapan Pengadilan Negeri di Surakarta. Penelitian ini menggunakan pendekatan sosiologi hukum dengan wawancara dan analisa terhadap beberapa penetapan dalam penyusunan paper. Artikel ini membahas pernikahan beda agama yang dilakukan masyarakat Indonesia yang mengalami kesulitan dan mengupayakan secara keras cara dalam pernikahan beda agama. Argumen lain artikel ini adalah pola penafsiran hukum yang beragam dari pasal-pasal Kompilasi Hukum Islam dan Undang-Undang Perkawinan. Tafsir ini membawa pada ketidakmapanan dan ketidakpastian hukum terkait dengan ketentuan pernikahan beda agama di Indonesia.]